2005
DOI: 10.1002/marc.200400482
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hyperbranched and Linear Polyglycidol Unimolecular Reverse Micelles as Nanoreactors and Nanocapsules

Abstract: Summary: Amphiphilic‐hyperbranched polyglycidols and a linear analogue were tested for their ability to act as nanoreactors for the unimolecular elimination (E1) reactions of tert‐alkyl iodides. Their encapsulation properties were also compared. The linear polymer was found to have very good “unimolecular reverse micellar” characteristics as well, even though the results showed the advantages of a hyperbranched nature over a linear one. Our results stress the need for a direct comparison of branched and linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…In addition to the entropic corrections of the LCT, also the energetic corrections to the FH theory have to be determined. The first order mixing energy ( ) as well as the second order mixing energy ( ) can be expressed as a sum [56]: (38) where the contributions and are given in literature [56]. These contribution depend on the architecture via and additionally from the difference in interaction energy of component and , expressed by the three interaction parameters , , and .…”
Section: Lct For a Ternary Polymer Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the entropic corrections of the LCT, also the energetic corrections to the FH theory have to be determined. The first order mixing energy ( ) as well as the second order mixing energy ( ) can be expressed as a sum [56]: (38) where the contributions and are given in literature [56]. These contribution depend on the architecture via and additionally from the difference in interaction energy of component and , expressed by the three interaction parameters , , and .…”
Section: Lct For a Ternary Polymer Solutionmentioning
confidence: 99%
“…Based on these advantages of HBP different applications have been suggested, for instance possible implementations of HBP are discussed in the field of medicine [1][2][3][4][5][6][7][8], catalysis [9][10][11][12][13], membrane materials [14][15][16][17][18][19][20], chemical engineering [21][22][23][24], sensors [25][26][27][28], thermosets [29][30][31] or as rheological modifier [32,33]. Polymeric drug delivery systems offer great opportunities to effectively control the drug release in human body [34][35][36][37][38][39][40][41][42][43][44]. In addition dendrimers can be surface engineered to release the drug at desired site, that is, as targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…48 Up to now, water-soluble hyperbranched poly(glycidol) (HPG) has been used widely to prepare amphiphilic molecular nanocapsules because it is highly biocompatible and without evident animal toxicity, which could encapsulate polar guests from water. 34,[49][50][51][52][53][54][55][56][57][58][59][60] Peng et al 50 have obtained star-hyperbranched block copolymers of HPG-b-polystyrene using atom transfer radical polymerization; these have good structural formation for ionic conductivity. Brooks et al 60 have reported the use of amphiphilic HPG as nanoreators for unimolecular elimination reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various types of dendrimers, star polymers, and hyperbranched polymers have been synthesized and their properties were compared to the linear analogues. 23,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] easily than glycodendrimers and star-shaped glycopolymers. [71][72][73][74][75][76] Recently, we proposed that the ringopening multibranching polymerization of anhydro and dianhydro sugars as latent AB m -type monomers should be a convenient method of synthesizing hyperbranched glycopolymers with a novel spherical macromolecular architecture, [77][78][79][80][81][82][83] for example, the hyperbranched polysaccharides from the cationic polymerization of 1,6-anhydro--D-hexopyranose, the hyperbranched poly(2,5-anhydro-D-glucitol) from 1,2:5,6-dianhydro-D-mannitol, and the hyperbranched polytetritols of 1,4-anhydrotetritol and 2,3-anhydrotetritol.…”
Section: Introductionmentioning
confidence: 99%